Association of SARS-CoV-2 Infection With Serious Maternal Morbidity and Mortality From Obstetric Complications. Issue 4 (21st December 2022) - Metz, T.D.; Clifton, R.G.; Hughes, B.L.; Sandoval, G.J.; Grobman, W.A.; Saade, G.R.; Manuck, T.A.; Longo, M.; Sowles, A.; Clark, K.; Simhan, H.N.; Rouse, D.J.; et al.
Abstract : ( JAMA . 2022;327:748–759) While pregnant patients with COVID-19 are at an increased risk of severe maternal morbidity related to the virus, it is not clear whether SARS-CoV-2 also increases the risk of maternal morbidity related to obstetric complications. The most common causes of obstetric morbidity in the United States are hypertensive disorders of pregnancy, postpartum hemorrhage (PPH), and other infections. Patients with COVID-19 may receive fewer visits or be isolated, possibly delaying evaluation and treatment. COVID-19 can cause irregularities in coagulation and hypertension, which may also play a role in obstetric morbidity. This study investigated the effects of SARS-CoV-2 infection on the risk of maternal morbidity or mortality from obstetric complications including PPH, hypertensive disorders of pregnancy, or infections.